2001
DOI: 10.1248/bpb.24.1246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calpain on Hereditary Cataractous Rat, ICR/f.

Abstract: The ICR/f rat is a recessive-type hereditary cataractous strain. We previously reported that this mutant differs from normal in the composition of lens crystallins.1) Analysis of the cataractous lens crystallins showed remarkable decreases in g-, bB1-and bA3-crystallin contents. Also, the calcium content in the cataractous lenses was about 10-fold higher than in the normal lenses. Two-dimensional electrophoresis of the cataractous lens proteins revealed the loss of b-and acrystallins and the appearance of new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…3) In previous studies, we have reported that oxidative stress occurred in cataractous lens (ICR85). 16,21) In this study, we have found an increase in the phosphorylation of serine residues of truncated of a-crystallin in cataractous lens (ICR85). In conclusion, C-terminal truncation and phosphorylation of a-crystallin could both reduce its chaperone-like activity and lead to cataract formation.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…3) In previous studies, we have reported that oxidative stress occurred in cataractous lens (ICR85). 16,21) In this study, we have found an increase in the phosphorylation of serine residues of truncated of a-crystallin in cataractous lens (ICR85). In conclusion, C-terminal truncation and phosphorylation of a-crystallin could both reduce its chaperone-like activity and lead to cataract formation.…”
Section: Discussionmentioning
confidence: 57%
“…Isolation and purification of lens crystallins were performed according to the method of previous paper. 16) Briefly, 4 ml of the supernatant (lens water-soluble fraction) was applied to a Superose 12 column (1.6ϫ50 cm, Amersham Biotech) and eluted with 50 mM phosphate (pH 7.0) containing 150 mM NaCl, 1 mM EDTA, and 0.02% NaN 3 at a flow rate of 0.5 ml/min at room temperature. The eluates from the column were monitored by measuring absorbance at 280 nm.…”
Section: Maldi-tof Mass Spectrometry Analysis Of Digested Peptides Anmentioning
confidence: 99%
“…31,32) The Ca 2+ content in the cataractous lenses of ICR/f rats is about 10-fold higher than in the lenses of Wistar rats, and autolytic products formed by calpain can also be detected in cataractous lenses. 33,34) We also reported that excessive nitric oxide produces an increase in lipid peroxide, and that the elevated lipid peroxide levels cause an decrease in Ca 2+ -ATPase activity and increase in Ca 2+ content in ICR/f rat lenses during cataract development. 18,19) It is noteworthy that ICR/f rat cataracts are not related to diabetic cataracts, and that the mechanism of cataract development is similar to that of senile cataracts.…”
Section: Discussionmentioning
confidence: 83%
“…[10][11][12][13][14] The Ca 2ϩ content in the cataractous lenses of UPLR, SCR and ICR are higher than in the lenses of Wistar rats, and autolytic products formed by calpain can also be detected in cataractous lenses. 11,12,15,16) It is noteworthy that the cataracts formed in these rat models are not diabetic cataracts. Therefore, these rats have been used for studies to develop anti-cataract drugs.…”
mentioning
confidence: 80%